Development of Library Management Mobile Application using Object-Oriented Approach - Lau, Sian En; Abdullah, Noryusliza (Applied Information Technology And Computer Science, 2023)
The Library Management Mobile Application is proposed to replace the manual library management system at Sekolah Kebangsaan (Perempuan) Bandar Kluang, SKPBK. This application is developed to enable portability in daily library tasks among the students, teachers and administrator. Furthermore, this application also allows the NILAM Program to be performed digitally. Additionally, the implementation of the payment penalty module grants the users a cashless environment by using a payment gateway. The project is conducted based on the Iterative Software Development Methodology. Android Studio software and Firebase database are used to build the application. Generally, with the support of the Library Management Mobile Application, the flow of work in terms of library-related subjects will be more effective, and efficiency will progressively grow.